Associations between social inequality and tooth loss in a household sample of elderly Thai people aged ≥60 years old - Srisilapanan P. (Blackwell Munksgaard, 2015)
Objective: To assess the relationship between social inequality and the number of remaining teeth in an elderly Thai population. Background: Having twenty or more remaining teeth is an important indicator of optimal oral health in the elderly. Methods: The data for this study were derived from the Survey of Older Persons in Thailand, conducted by the National Statistical Office, based on face-to-face interviews with people aged ≥60. The total sample was 30 427. The oral health measure was self-reported remaining number of teeth. Income, education and possession of durable goods were utilised as measures of social inequality. Results: More than half of the sample (57.0%) was women. The majority (73.2%) was in the age range 60-74 years old. Less than a fifth (15.5%) had 7 or more years of education. A third earned <20 000 Thai Baht (THB) per annum (defined as poor). More than half (52.8%) of the sample had <20 remaining teeth. There was a link between social inequalities and tooth loss. In the adjusted model, elderly people, who were older than 75, who were not under a married status, had a lower level of education, had a lower income, and who did not own luxury goods, were 2.84 (CI 95% 2.66-3.03), 1.31 (CI 95% 1.21-1.41), 1.44 (CI 95% 1.34-1.56), 1.12 (CI 95% 1.13-1.29) and 1.21 (CI 95% 1.13-1.29) times more likely to have 19 or fewer teeth remaining, respectively. Conclusion: Social inequality is related to the number of remaining teeth in elderly Thai people. © 2014 John Wiley & Sons A/S and The Gerodontology Association.